Synthesis of Chalcogenides and Metal Complex of 2-Phenyl-benzo[ 1,3,2]dioxophosphinin-4-one - Rani, Manju; Kumar Shukla, Davender; Ali Khan, Arif (Asian Journal of Chemistry, 2014)
The chalcogenides and the metal complexes of 2-phenyl-benzo[1,3,2]dioxophosphinin-4-one are prepared by single step reaction of 2-phenyl-benzo[1,3,2]dioxophosphinin-4-one (1) with DMSO, elemental S, Se and W(CO)5CH3CN.